Analisis Manfaat Program Corporate Social Responsibility (CSR) PT Djarum Bagi Dinas Perumahan, Kawasan Permukiman dan Lingkungan Hidup (PKPLH) Kabupaten Kudus dan Masyarakat Studi Kasus: Konservasi Lereng Muria (KLM) - Muhammad Alfian Afif; Ahmad Taufiq (Journal of Politic and Government Studies, 2018)
Initially, the concept of CSR was motivated by the motivation of Charity companies. The goal is to look for negative ones that come from the community like destroying the environment and only pursue short-term profits on that day. There are now many companies that carry out social responsibility through various programs. One of them is PT Djarum through the Djarum Foundation Division. The Djarum Foundation carries out various types of CSR programs, one of which is the conservation of muria slopes (KLM).This study uses the Theory of the Principles of implementing CSR programs to find out how the Muria Slope Conservation program is implemented by the Djarum Foundation and uses policies on the types of CSR Programs to determine the objectives and benefits of the Muria Slope Conservation Program. The research was conducted with qualitative research methods. Data collection is done through interviews with resource persons and based on findings in the field.The results of the research that has been done are, in this study it is known that in implementing the CSR program Slope Conservation Muria Djarum Foundation applies the principles of implementing CSR. It is also known that the Muria Slope Conservation program is included in the type of socially responsible business practice program because it encourages social problems to improve the community and the environment by using plant seeds and planting on critical land. In implementing the KLM Djarum Foundation and PKPLH Service programs because they have data and information relevant to the environmental conditions in Kudus. The benefits that can be accessed by the PKPLH Office are that they are greatly helped by the KLM program. Then another benefit that is gained is that in carrying out the work program, the PKPLH Service can request assistance from the Djarum Foundation. The benefits that can be accessed by the community are those who can help them and can access the conditions around the slope of the muria to be normal. The Djarum Foundation and PKPLH Office have carried out more than 70,000 seeds from 15 types of plants and have planted in 7 (seven) villages on the slopes of the muria.Keywords: CSR, Muria Slope Conservation (KLM), partnership